The Legacy of Jonathan Edwards in the Theology of Andrew Fuller - Chun, Chris (Leiden : BRILL, 2012)
This study positions itself in the transatlantic, early modern period between American Congregationalist Jonathan Edwards (1703- 1758) and English Baptist Andrew Fuller (1754-1815), and their attempts to express au fait understanding of reformed soteriologcial ideas in the age of reason.
5.1.1 Sandemanianism in Scotland6. Fuller's View of Atonement and the New England Theologians; 7. Edwards's Influence on Fuller's Conception of 'Justification by Faith'; Conclusion: The Legacy of Jonathan Edwards in the Theology of Andrew Fuller; Appendix: Fuller's Access to Published Literature of Edwards in Britain; II. Secondary Sources; a. Monograph, Books and Booklets; b. Journal Articles, Encyclopedia, Chapters in Collected Works.
Description based on print version record.
Keywords: Baptists -- Doctrines; Edwards, Jonathan, 1703-1758 -- Influence; Fuller, Andrew, 1754-1815.; Religion; Edwards, Jonathan, -- 1703-1758 -- Influence; Fuller, Andrew, -- 1754-1815.; Baptists -- Doctrines; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Electronic books